A four‐stream method for providing variable dialysis fluid bicarbonate concentrations for bicarbonate‐based dialysis fluid delivery systems. Issue 12 (21st October 2021) - Lew, Susie Q.; Sam, Ramin; Tzamaloukas, Antonios H.; Ing, Todd S.
Abstract: Background: Hemodialysis corrects metabolic acidosis by transferring bicarbonate or bicarbonate equivalents across the dialysis membrane from the dialysis fluid to the plasma. With the conventional three‐stream bicarbonate‐based dialysis fluid delivery system, a change in the bicarbonate concentration results in changes in the other electrolytes. In practice, the dialysis machine draws either a little less or more from the bicarbonate concentrate and a little more or less from the acid concentrate, respectively in a three‐stream delivery system. The result not only changes the bicarbonate concentration of the final dialysis fluid but also causes a minor change in the other ingredients. Methods: We propose a four‐stream bicarbonate‐based dialysis fluid delivery system consisting of an acid concentrate, a base concentrate, a product water, and a new sodium chloride concentrate. Results: By adjusting the flow rate ratio between the sodium chloride and sodium bicarbonate concentrates, one can achieve the desired bicarbonate concentration in the dialysis fluid without changing the concentration of sodium or ingredients in the acid concentrate. The chloride concentration mirrors the change in bicarbonate but in the opposite direction. Conclusion: A four‐stream, bicarbonate‐based dialysis fluid delivery system allows the bicarbonate concentration to be changed without changing the other constituents of the final dialysis fluid. Abstract : We propose a four‐stream bicarbonate‐based delivery system consisting of an acid concentrate (A ), a base concentrate (B ), a product water, and a new sodium chloride concentrate (S ). By adjusting the flow rate ratio between the sodium chloride and sodium bicarbonate concentrates, one can achieve the desired bicarbonate concentration in the dialysis fluid without changing the concentration of sodium or ingredients in the acid concentrate. The chloride concentration mirrors the change in bicarbonate but in the opposite direction.